Peran Lembaga Perbankan Dalam Pemberdayaan Usaha Kecil Masyarakat Lokal di Kota Jayapura - Ketaren, Dahliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine, analyze, and explain the role of banking institutions in empowering small businesses of local communities in Jayapura City and empowerment regulations involving the Chamber of Commerce and Industry (KADIN) and the Papuan Customary Chamber of Entrepreneurs (KAPP Papua). The research method is empirical law which is based on the idea that law is inseparable from the lives of its people in the form of values and attitudes/behaviors carried out (non-autonomous law), so that the study of law does not only concern normative aspects, but law can be studied from its empirical aspect, namely how the law is in reality in the lives of the community. The results of this study reveal that after the enactment of special autonomy for Papua Province, the empowerment of small businesses of indigenous Papuans has not been carried out optimally by the Provincial Government, Regency and Jayapura City, so that it is not in accordance with the application of the theory of justice which emphasizes that justice is fairness and should always be fought for through correlation and improvement of social institutions, economic institutions, and other institutions through agreements that are used as a legal basis to be directed towards justice for all interested parties. Likewise, the role of banking institutions has not been maximized, because loans in the form of MSME credit and KUR are hampered by collateral problems. Since there are no specific forms of empowerment for small businesses, the Regency/City Government needs to create a Regional Regulation (PERDA) on small businesses for indigenous Papuans so that they have access to sources of financing and guarantees in efforts to empower small businesses for indigenous Papuans.